Early Treatment of Unilaterally Severe Horizontally Impacted Maxillary Central and Transversely Impacted Lateral Incisors - Lertnimulchai, Supachai; Godfrey, Keith; Lertnimulchai, Rewadee (Thai Journal of Orthodontics, 2020)
This case report records the sequential management of a transversely impacted lateral incisor and adjacent severe horizontally impacted central incisor in a Thai girl aged 8 years and 9 months. The treatment protocol consisted of multidisciplinary management, combining orthodontics, surgery, periodontics and good patient’s compliance. The treatment resulted in good esthetics and function, and good periodontal health.